Implementasi Kebijakan Sertifikasi Tanah Wakaf dalam Menghadapi Rendahnya Kesadaran Masyarakat dan Sengketa Waris di Bidang Zakat Wakaf (ZAWA) Kementerian Agama Kabupaten Temanggung Tahun 2025 - Astriani, Dia Dia; Aziz, Abdul (Mafa Press, 2025)
This study examines the implementation of the waqf land certification policy in Temanggung Regency as an effort to strengthen the legal status of waqf assets and support their use for community welfare. A descriptive qualitative approach was employed, using field observation, interviews with officials from the Ministry of Religious Affairs of Temanggung Regency, the National Land Agency (BPN), and nazhir, as well as policy document review. Data analysis followed George C. Edwards III’s policy implementation model: communication, resources, implementers’ disposition, and bureaucratic structure. The findings indicate that the free certification program has improved legal certainty and encouraged nazhir to formalize uncertified waqf land. However, several obstacles persist, including administrative delays, inheritance disputes, limited human resource capacity and digital systems, and procedural inconsistencies between sub-districts. The study recommends strengthening public outreach, building nazhir capacity, simplifying inter-agency coordination, and accelerating integrated waqf data systems. Overall, land certification is a critical step in shifting waqf from a primarily consumptive role toward a productive instrument for local socio-economic empowerment.